Peran Pemerintah dalam Optimalisasi Pelaksanaan Peremajaan Tanaman Kelapa Sawit - Asri Elies Alamanda (Universitas Batanghari Jambi, 2023)
Palm oil is one of the leading agricultural sectors which has an important role in Indonesia. In addition to being able to absorb new workers, the oil palm plantation business can also contribute to state revenues from crude palm oil (CPO) export levies, the demand for which is increasing every year. However, in recent years the level of productivity of oil palm plantations has decreased. This is due to the age of the plants that are getting older and not using superior and certified seeds at the start of planting. With this low level of productivity, it is necessary to carry out rejuvenation of oil palm plants. The target of this rejuvenation program is to be able to use both superior and certified seeds in order to increase plant productivity. This research uses normative juridical research methods, namely research conducted by researching and analyzing literature or secondary data only. The approach method is descriptive and qualitative research methods. The results showed that the government played an active role in implementing the oil palm rejuvenation program. This is evident from the many regulations made by the government or other stakeholders to support the smooth running of this program. In addition, as an effort to provide support in increasing palm oil productivity, especially in preparing funds for rejuvenation programs, the government has established the Oil Palm Plantation Fund (DPKS).